Durability increase of gear pumps in agricultural machinery - Прасолов, Евгений Яковлевич; Семененко, Роман Сергійович (Technology audit and production reserves, 2014)
The analysis of the literature on the issue of durability performance providing of gear pump tribocoupling of tractor hydraulic system is made. The laboratory unit and optimal composition of cutting fluid with antifriction additives for tribocoupling condition research is proposed. According to experimental results it is determined that the efficiency improvement of pump tribocoupling is due to the optimal composition of cutting fluid with antifriction additives. The optimal structure of the basis for additives is determined. A comparative study on the friction machine showed the improvement of tribocoupling properties of samples that were processed by piercing using cutting fluid with antifriction additives. It is determined that the use of antifriction additives decreases the friction torque, increases wear resistance and load setting, accelerates the grinding process of the tribocoupling friction pair details of НШ-32-У pump. The technology of economically and efficiently carrying out of plugs pump restoration through the use of combined piercing and antifriction additives in cutting fluid is grounded and shown.